Quantitative analysis of money cycle and economic stability in economocracy - Challoumis, Constantinos (Research Papers in Economics and Finance, 2024)
The paper discusses economocracy and representative econo-mocracy as innovative approaches proposed by author. These new economic systems, analogous to the political system of de-mocracy, aim at managing global debt and promoting economic sustainability. Economocracy is presented as a reformed economic system, distinct from capitalism, that incorporates the mechanisms of a free-market economy to address disruptions such as wars (re-construction of countries), recessions and economic crises. The results imply that economocracy has the potential to provide so-lutions to global economic issues by effectively circulating capital while promoting democratic governance and stable economies. The research involves a quantitative analysis of economic mod-els, specifically focusing on the Economic Productive Reset (EPR) and Economic Periodic Injections (EPI) as tools to alleviate global indebtedness and maintain economic stability.